Sign Pairity Difference Cordial Labeling of Digraphs. Issue 1 (June 2021) - Palani, K.; Nivetha, S.; Nagarajan, A.
Abstract: Let D = ( V, A )be a digraph. An injective function f : V ( D ) → 1, 2, …. p is said to be a sign pairity difference cordial labeling if the induced arc labeling f ∗ : A ( D ) → 0, 1 defined by f ∗ (( μ, ν )) = 1 iff ( u ) − f ( v ) > 0 0 elsewhere satisfiesthe condition that | e f 0- e f (1)| ≤ 1 where, e f (0) is the number of arcs with label 0 and e f (1) is the number of arcs with label 1. In this paper, we analyze the existence of sign pairity difference cordial labeling in the digraphs Directed Path ( P n → ) ( A P n → ), Directed Cycle ( C n → ), Outstar ( o K 1, n → ), Inwheel ( i W n → ) and Downcomb ( Down P n ⊙ K 1 → ) defined by K.Palani et.al.,